THE AUTHORITY OF TEACHER IN MERDEKA BELAJAR DISCOURSE - Rohmad, Muhammad Ali (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2020)
ABSTRACTEducation policy in Indonesia often changes lately, it makes education practitioners uneasy. It is feared that this will affect the teacher's authority. So this study aims to determine the authority of the teacher in the Merdeka Belajar discourse. After reviewing the study of literature, it can be concluded that; 1) By using a new USBN model, teachers were very likely to be more authoritative because student graduation was determined by teachers and schools; 2) UN by using the Minimum Competency Assessment and Character Survey ware expected to create an authoritative evaluation system without cheating; 3) Simple lesson plans gave an extensive time for teachers and students together and increased the authority of teachers; and 4) PPDB zoning system which reduced the percentage of zone line, was actually not directly related to the authority of teachers, whereas it made students’ academic competition increasing.Keywords: Authority, Teacher, Merdeka Belajar.